RUSSIAN LANGUAGE ALPHABET FROM THE REVOLUTION OF 1917 IN RUSSIA UNTIL TODAY (RUSSIAN-CHINESE PARALLELS) - A. N. Aleksakhin (Концепт: философия, религия, культура, 2017)
The creation and changing of alphabets, as shown by their history, occurs due to the development needs of human communities, united by one language in certain public national entities. The alphabets as systems of different letters denote the system of phonemes as basic units or atoms of a particular language at a certain stage of its development. Objectively, regardless of the person, languages are developing in their natural matters which are the sounds of speech. Alphabets can be modified and improved by people, cognizing objective language derivative laws intuitively and efficiently. Even a few letters adding or deleting from the alphabet is mated with the change of spelling of a large number of words within a certain language which is perceived ambiguously and painfully by those who are reading and writing it. And there is no surprise that writing systems transformations within Russian and Chinese languages have been implemented during the revolution. In both countries the need for the reform of the writing system has been maturing for centuries in the direction of its democratization and accessibility for the vast majority of the illiterate population of Russia and China.